PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK PADA MATERI BANGUN DATAR SEGIEMPAT SMP/MTs - Vivi Warni; Kartini '; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is the lack of availability mathematics learning instrument based curicullum 2013 by teachers. This research purpose is produce to mathematics learning instrument (Lesson Plan and Student Worksheet) which refers to Realistic Mathematics Education (RME) on matter of build flat quadrilaeral for SMP/MTs. This reserch method used is 4D model by Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel that consist of define, design, development, and disseminate, but the reserch only done to development step. Based on the results, data analysis can be concluded that the study of mathematics is very valid to the average ratings for the lesson plan is 3.85 and the average ratings for the student worksheet is 3.82. The student worksheet has also reached the practical qualification in mean percentage of student responses 97.5% in small group trial and 97% in large group trial.